Methodology for the Estimation of Annual population stocks by citi-zenship group, age and sex in the EU and EFTA countries - Bijak, J.; Kupiszewska, D. (Informatica)
Methodology for the Estimation of Annual population stocks by citi-zenship group, age and sex in the EU and EFTA countries